GUIDELINES FOR ENHANCING DESIRED CHARACTERISTICS IN SCHOOLS UNDER THE PRIMARY EDUCATION SERVICE AREA OFFICE - Chuaibamrung, Arkom (Journal of MCU Nakhondhat, 2022)
The objective of this academic article was To discuss the knowledge of desired characteristics in schools in order to ensure proper measurement and evaluation. and To create guidelines for Enhancing desired characteristics in schools under the Primary Education Service Area Office which consists of concepts of desired characteristics. Desired characteristics according to the Basic Education Core Curriculum of B.E. 2551 (A.D.2008). Guidelines for measuring and evaluating desired characteristics according to the Basic Education Core Curriculum of B.E. 2551 (A.D.2008). And guidelines for enhancing desired characteristics of primary schools. Desirable Characteristics It is a characteristic that is desired to happen to the learners. It is a characteristic that society needs in terms of morality, ethics, values, conscience, good character and good character. and can live happily with others in society If the lack of impact on the individual is to cause trouble for themselves, others and society, which development and strengthening should start from school-age children because it is an age that is easy to learn and remember. It is also the age that begins to learn the rules of society according to Kohlberg's theory of ethical development. Therefore, cultivating desirable qualities in children and youth is important. Guidelines for Enhancing and developing desirable characteristics in primary schools This can be done by applying the definitions, indicators, indicative behaviors or expressed behaviors of each of the analyzed attributes. integration in learning activities of various learning subject groups; learner development activities Various special projects that educational institutions can create When educational management has instilled desirable characteristics for everyone to be good people in the form that society wants. The society can get good quality people, it is an important choice to develop and solve Thailand's problems in the future.